The coping strategies of syrian adolescent refugee in Malaysia: A case study - Mukhtar Ahmed, Iman Osman (Opción, 2019)
In this paper qualitative approach was utilized to interview 11 Syrian adolescent refugees, 9 parents and 2 teachers in Malaysia. In-depth interviews were conducted to explore the participants’ coping strategies with war experiences and the difficulties they face in Malaysia. The results showed participants used religious beliefs and spiritual coping, cognitive strategies such as developing positive attitudes, acceptance coping, and use of hope as coping strategies. Social support, socialization and social media were among the most significant external resources for coping strategies. Activities and enhancement of self-skills are the most important factors for personal coping with disasters and war trauma